The Implications of Paraspinal Muscle Atrophy in Low Back Pain, Thoracolumbar Pathology, and Clinical Outcomes After Spine Surgery: A Review of the Literature. Issue 5 (August 2020) - He, Kevin; Head, Jeffery; Mouchtouris, Nikolaos; Hines, Kevin; Shea, Phelan; Schmidt, Richard; Hoelscher, Christian; Stricsek, Geoffrey; Harrop, James; Sharan, Ashwini
Study Design: Literature review. Objectives: Paraspinal muscle integrity is believed to play a critical role in low back pain (LBP) and numerous spinal deformity diseases and other pain pathologies. The influence of paraspinal muscle atrophy (PMA) on the clinical and radiographic success of spinal surgery has not been established. We aim to survey the literature in order to evaluate the impact of paraspinal muscle atrophy on low back pain, spine pathologies, and postoperative outcomes of spinal surgery. Methods: A review of the literature was conducted using a total of 267 articles identified from a search of the PubMed database and additional resources. A full-text review was conducted of 180 articles, which were assessed based on criteria that included an objective assessment of PMA in addition to measuring its relationship to LBP, thoracolumbar pathology, or surgical outcomes. Results: A total of 34 studies were included in this review. The literature on PMA illustrates an association between LBP and both decreased cross-sectional area and increased fatty infiltration of paraspinal musculature. Atrophy of the erector spinae and psoas muscles have been associated with spinal stenosis, isthmic spondylolisthesis, facet arthropathy, degenerative lumbar kyphosis. A number of studies have also demonstrated an association between PMA and worse postoperative outcomes. Conclusions: PMA is linked to several spinal pathologies and some studies demonstrate an association with worse postoperative outcomes following spinal surgery. There is a need for further research to establish a relationship between preoperative paraspinal muscle integrity and postoperative success, with the potential for guiding surgical decision making.